Country patterns of behavior on broader dimensions of human development - Gustav Ranis; Frances Stewart; Emma Samman (Yale University, Economic Growth Center, 2007)
This paper adopts a more expansive definition of Human Development than that encompassed by the Human Development Index in order to explore diverse country patterns of behavior in relation to these broadened dimensions. We proceed by first identifying the dimensions to be investigated and subsequently present the methodology adopted for clarifying country behavior with respect to these dimensions. Countries are shown to differ substantially in terms of their choices among the independent dimensions of well-being which may or may not be constrained by history or culture. We then group countries by level of per capita income, experience with internal conflict, region of the world, oil, wealth, distance from the equator, distance from the sea, in the search for identifiable differential behavior patterns by country typology. We find that choices do exist across the board. For example, even low income countries can achieve well in all categories while high income countries do poorly.
Keywords: I31; O15; O57; 330; Human development; quality of life; happiness; capabilities; country behavior